2021
DOI: 10.3390/nano11112934
|View full text |Cite
|
Sign up to set email alerts
|

The Ripple Effect of Graphite Nanofilm on Stretchable Polydimethylsiloxane for Optical Sensing

Abstract: Graphene-based optical sensing devices have been widely studied for their broad band absorption, high carrier mobility, and mechanical flexibility. Due to graphene’s weak light absorption, studies on graphene-based optical sensing thus far have focused on hybrid heterostructure devices to enhance photo-absorption. Such hybrid devices need a complicated integration process and lead to deteriorating carrier mobility as a result of heterogeneous interfaces. Rippled or wrinkled graphene has been studied in electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Designing an innovative PD device using Si film is considered a novel approach for image sensors (see Figure a) . Electronic and optoelectronic devices have been studied with rippled or wrinkled graphene, which revealed that an increase in ripple density of graphite nanostructures with the help of a supporting PDMS layer, the photoresponsivity also increased (see Figure b) . The graphene-based photodetector systems concentrated on hybrid technology to boost photoabsorption.…”
Section: Technological Evolution Of Image Sensing: An Overview On Cur...mentioning
confidence: 99%
See 2 more Smart Citations
“…Designing an innovative PD device using Si film is considered a novel approach for image sensors (see Figure a) . Electronic and optoelectronic devices have been studied with rippled or wrinkled graphene, which revealed that an increase in ripple density of graphite nanostructures with the help of a supporting PDMS layer, the photoresponsivity also increased (see Figure b) . The graphene-based photodetector systems concentrated on hybrid technology to boost photoabsorption.…”
Section: Technological Evolution Of Image Sensing: An Overview On Cur...mentioning
confidence: 99%
“…(b) Process of fabrication in rippled graphite (rGr) nanofilm-based image sensor. Reproduced with permission from ref . Copyright 2022 MDPI.…”
Section: Technological Evolution Of Image Sensing: An Overview On Cur...mentioning
confidence: 99%
See 1 more Smart Citation
“…11 It comprises a monolayer of carbon atoms arranged in a hexagon network. 7,18–42 Thus, graphene has been shown as a greatly promising material for future optoelectronic devices due to its remarkable features, including high mobility reaching up to 10 4 cm 2 V −1 s −1 at ambient temperature, exceptional thermal and electric conductivities, and ballistic transport. 12,43 Also, in the broad spectra range of visible and near-infrared (NIR), the transmittance of single layer graphene can reach 97.7%, and only 2.3% of the light intensity can be absorbed.…”
Section: Emergence Of Graphene/si In Solar Cells and Photovoltaicsmentioning
confidence: 99%
“…Graphite and graphene show superior properties over Si and are considered as potential material for a next-generation semiconductor and display devices to replace currently limited device technologies [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. In addition, graphite and graphene have also exhibited mechanical flexibility and transparency, which are highly desirable for wearable devices or detection applications [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Compared to other 2D materials, graphene is much more mature for large-scale mass production.…”
Section: Introductionmentioning
confidence: 99%